Studi Ekonomi Politik Youtube: Komodifikasi Subscriber Channel Ricis Official - Ahsani Taqwim Aminuddin; Aen Istianah Afiati (KAGANGA KOMUNIKA: Journal of Communication Science, 2023)
The thing that makes YouTube in great demand as a place of work is the monetization of viewer numbers and the various tools it provides. This makes YouTubers appear to be competing to produce videos with many views. This practice is predicted to become the forerunner of the practice of audience commodification because monetization on Youtube is calculated based on the number of views. This study uses a qualitative descriptive method with primary and secondary data sources. Primary data were obtained from interviews with the Official Ricis channel management and some viewers from the Ricis Official Youtube Channel. The author obtained secondary data from Ria Ricis' video talk shows on the internet, journals, media coverage, and other related literature. The results of this study note that the form of commodification of audiences on the Ria Ricis Youtube channel occurs in various ways, starting with personal branding that adapts to the targeted audience. The content that is produced is then promoted on various social media to invite more and more viewers. Interested audiences don't mind any content uploaded (naturalized). The audience feels comfortable with whatever Ria Ricis presents, while the content creator tends to present videos that he thinks will only attract a lot of views.   Keywords: Audience Commodification, Social Media, Political Economy, Youtube